An antiderivative of the function x 6 + 1 x 3 − x can be expressed as 3 1 ln ( d x 2 + 1 a x 4 − b x 2 + c ) + C , where a , b , c , d are constants, and C denotes the arbitrary constant of integration .
Find the smallest possible value of a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Multiple answers possible . Also, you had already put a negative sign with b x 2 in given statement. Then why u took b = − 4 . @Muhammad Alif
Log in to reply
Oh sorry, I will correct that, thanks @C Anshul
I = ∫ x 6 + 1 x 3 − x d x = ∫ ( x 2 + 1 ) ( x 4 − x 2 + 1 ) x 3 − x d x = ∫ ( 3 ( x 2 + 1 ) − 2 x + 3 ( x 4 − x 2 + 1 ) 2 x 3 − x ) d x = ∫ ( 3 ( x 2 + 1 ) − 2 x + 3 ( x 2 + 3 x + 1 ) ( x 2 − 3 x + 1 ) 2 x 3 − x ) d x = ∫ ( 3 ( x 2 + 1 ) − 2 x + 6 ( x 2 + 3 x + 1 ) 2 x + 3 + 6 ( x 2 − 3 x + 1 ) 2 x − 3 ) d x = − 3 ln ( x 2 + 1 ) + 6 ln ( x 2 + 3 x + 1 ) + 6 ln ( x 2 − 3 x + 1 ) + C = 3 1 ln ( x 2 + 1 x 4 − x 2 + 1 ) + C By partial fraction decomposition By partial fraction decomposition again where C is the arbitrary constant of integration.
Therefore, a + b + c + d = 1 + 1 + 1 + 1 = 4
Problem Loading...
Note Loading...
Set Loading...
∫ x 6 + 1 x ( x 2 − 1 ) d t ---> assume : x 2 = a ---> 2 x d x = d a
---> 2 1 ∫ a 3 + 1 a − 1 d a = 2 1 ∫ ( a + 1 ) ( a 2 − a + 1 ) a − 1 d a
---> ( a + 1 ) ( a 2 − a + 1 ) a − 1 = a + 1 P − a 2 − a + 1 Q a + R
a − 1 = ( P − Q ) a 2 + ( − P − Q − R ) a + ( P − R ) ---> P = Q = − 3 2 , R = 3 1
---> 2 1 ∫ ( a + 1 ) ( a 2 − a + 1 ) a − 1 d a = 6 1 ∫ ( a + 1 − 2 + a 2 − a + 1 2 a − 1 ) d a
We must evaluate the integral of ∫ a 2 − a + 1 2 a − 1 d a first :
---> ∫ a 2 − a + 1 2 a − 1 d a = 4 ∫ ( 2 a − 1 ) 2 + 3 2 a − 1 d a
---> consider : 2 3 t a n θ = 2 a − 1 ---> a = 2 2 3 t a n θ + 1 ---> d a = 2 2 3 s e c 2 θ d θ
2 ∫ 3 . s e c 2 θ 2 3 . t a n θ 2 3 s e c 2 θ d θ = 2 ∫ tan θ d θ = − 2 . l n ∣ c o s θ ∣ = − 2 l n ∣ 2 4 a 2 − 4 a + 4 2 3 ∣ + C
Then, we have :
6 1 ∫ ( a + 1 − 2 + a 2 − a + 1 2 a − 1 ) d a = 6 1 ( − 2 . l n ∣ a + 1 ∣ − 2 l n ∣ 2 4 a 2 − 4 a + 4 2 3 ∣ + C ) = 3 1 . l n ∣ 2 3 ( x 2 + 1 ) 2 4 x 4 − 4 x 2 + 4 ∣ + K , K = 6 1 C
---> I.e the desired value is 4 − 4 + 4 + 1 = 5